Histochemical Studies on the Different Nuclei of Hypothalamus of Indian Buffalo during Different Reproductive Stages - Pathak, Devendra; Bansal , Neelam (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was aimed to elucidate the histochemical moieties in different nuclei in the hypothalamus of Indian buffaloes under different  reproductive stages. Tissue samples were collected from three levels, the supraoptic region (anterior region), the tuberal region (middle  region), and the mamillary region (posterior region) of the hypothalamus, and processed for routine histochemical studies and cryo sectioning. The paraffin sections were stained for carbohydrate and protein localization, while the cryosections were used for lipid  demonstration. The neurosecretory substance of the neurons in these nuclei was PAS-positive and mostly clustered along the periphery  of the cell. An intense reaction of acid mucopolysaccharides was also present in the peripheral part of the perikaryon and weak nucleus.  The neurosecretory materials were noticed in the perikaryon and axon fibers of the paraventricular nucleus. A strongly positive reaction  for PAS -Alcian blue was observed in the neurons of all the reproductive phases. The neurons in the arcuate nucleus demonstrated  intense PAS reaction in the peripheral part of the neuron during the follicular phase and pregnant buffaloes. The PAS reaction was  moderate during the luteal phase and weak in prepubertal buffaloes. The reaction product was granular. Acid mucopolysaccharides  (AMPS) were also strongly present in these neurons during the follicular phase and in pregnant animals. PAS reactive neurosecretory  granules were observed in the perikaryon of neurons located in the ventromedial nucleus. AMPS were also located in the cytoplasm of  these neurons. The reaction was moderate to strong in pubertal buffaloes while moderate in prepubertal buffaloes. Sudanophilic lipid  droplets and Oil Red O positive lipids were observed in the neuronal substance of preoptic, supraoptic, and paraventricular nuclei of  the buffalo hypothalamus during the pubertal period.
Keywords: Histochemical Studies; Hypothalamus; Indian Buffalo; Nuclei